Evaluasi Pembelajaran Membaca Permulaan di Kelas Awal Sekolah Dasar - Asep Muhyidin (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2017)
The objective of the research was to understand comprehensively the early reading learning at class II Public Elementary School Serang 2, Serang City, Banten Province. The method used in this research is qualitative research. The data were collected through participant observation using interview, observation, and document study. The research finding shows the evaluation on early reading learning: 1)the result evaluation, and 2) the process evaluation.